Mrs. T.C. Worly visiting with Mrs. John Goldsborough - Unknown:::Creator::::::::::::
Photograph shows Mrs. T. C. Worly, vice president of the Good Samaritan Hospital Auxiliary (left) visiting with Mrs. John Goldsborough who is a YWCA board member. They are sitting in chairs and are holding plates in their laps. The photograph was taken for the San Jose News on Friday April 2, 1965.